Lean into Clinical Pharmacy: An Experience in Implementing Key Performance Indicators and Gemba Walks into Clinical Pharmacy Services - Jocelyn Owusu-Guha; Connie Yoon; Jordan DeWitt; Pamela L. Buschur; Jennifer Bauer; Adam Smith; Abby Tyson (University of Minnesota Libraries Publishing, 2021)
Purpose: The Lean methodology was applied to clinical metrics by a critical care pharmacy team. The experiences associated with the development and implementation of clinical metrics and their impact on daily workflow are described. Summary: The Lean methodology has been introduced into the healthcare system as a means of process improvement, which can eliminate waste through appropriate medication utilization. At OhioHealth Riverside Methodist Hospital, the department of pharmacy was tasked with the development of clinical metrics after a health system wide Gemba walk was initiated. The pharmacy department's critical care team developed a strategy identifying and evaluating clinical metrics pertaining to their everyday workflow. Each clinical metric was evaluated in accordance with a pre-defined goal. Metrics requiring heavy documentation and those in which the pharmacist does not have autonomous authority to manage were often challenging to implement and were less successful. Throughout this process, the lessons learned focused on generating ideas that were easily documented, evidence-based, and department specific. The critical care team discovered that the outcome of the most successful metrics highlighted clinical pharmacist value and data generated could be used to support funding for additional resources. Conclusion: The critical care pharmacy team developed a streamlined process to implement clinical metrics as means of identifying areas for improvement using the Lean methodology.